Goal Modification, Learning Styles, and Achievement in Mathematics - Joaquin, Ma. Nympha B.; Ganaden, Mildred S.; Ibe, Milagros D. (Philippine Journal of Education Studies (formerly the Education Quarterly); Vol. 66, No. 1 (December 2008), 2010)
This study investigated whether mastery and competitive goals could be developed among students, while controlling for the possible effects of student learning styles. A pretest-posttest control group design was used in this 10-week experiment that employed three intact high school mathematics classes. Results showed that mastery and competitive goals could be separately modified among students. However, learning styles did not moderate the effects of these goal modifications. The study further investigated which of the three goals – mastery, competitive, and avoidance – predicts achievement in mathematics. The outcome showed that each of the three goals linearly predicts mathematics achievement. However, when the effects of all three goals were simultaneously considered, only avoidance goals remained as a predictor of achievement. It is recommended that further investigations be made on the possible classification of avoidance goals into projective, compliance, and work-avoidance goals. Moreover, the positive potential of projective goals should be explored.